2020
DOI: 10.1049/iet-com.2019.0206
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs between the quality of service, computational cost and cooling complexity in interference‐dominated multi‐user SDMA systems

Abstract: The future fifth generation (5G) systems will aim to design low-cost phased array base station antenna systems at mm-waves for simultaneous multiple beamforming with enhanced spatial multiplexing, limited interference, acceptable power consumption, suitable processing complexity, and passive cooling. In this study, a multiuser space division multiple access (SDMA) model is developed to investigate the trade-off between the quality of service (QoS), computational complexity in beamforming and cooling requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…(D-ii) The number of simultaneously served far-away users (that need the gain from all the subarrays) is limited by the number of BM ports. However, in [32], it was shown that the number of users cannot be very large (K, P < 8 for the current chip technologies) due to the thermal management problems which is preferred to be handled passively via natural convection [33].…”
Section: The Major Advantages (A-i-a-v) / Disadvantages (D-i-div) Of mentioning
confidence: 99%
“…(D-ii) The number of simultaneously served far-away users (that need the gain from all the subarrays) is limited by the number of BM ports. However, in [32], it was shown that the number of users cannot be very large (K, P < 8 for the current chip technologies) due to the thermal management problems which is preferred to be handled passively via natural convection [33].…”
Section: The Major Advantages (A-i-a-v) / Disadvantages (D-i-div) Of mentioning
confidence: 99%
“…However, in [21] it was showed that a potential increase in the channel capacity can be obtained by exploiting an irregular antenna array layout. Planar array topologies based on irregular layouts have been designed by using convex optimization technique with the aim of decreasing the Peak-Side-Lobe-Level (PSLL) [22]- [25]. It has to be observed that the reduction of the PSLL by aperiodic arrangements is obtained by spreading the energy in a larger solid angle, thus raising the Average Side Lobe Level (ASLL) [26] with a consequent maximum array gain reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of the next generation communication network, with the potential use of the millimeter wave (mmwave) frequencies for high-throughput, brings up many severe system challenges including, but not limited to, the increased product cost, implementation complexity, processing burden and heat generation [1]. Although it is foreseen that digital beamforming solutions will prevail in the future due to their ability to provide the most flexible, accurate and versatile performance, currently, the industrial baseline for beamforming in 5G antennas are mostly based on analog architectures that can generate a single beam at a time [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth to mention here that according to the beamwidth (and depending on the cell size), it might be necessary to adjust the input power to satisfy the demanding 5G mm-wave link budget requirements. Additionally, in 5G, it is desired, for each beam with a different resolution, to have a wide-angle scanning capability with low side lobe levels (SLLs) in order to ensure a high Quality-of-Service (QoS) in the statistical sense [1].…”
Section: Introductionmentioning
confidence: 99%